Social identity - Wearing, Michael, 1961- (Social issues, justice and status series., 2011)
Social identity theory is a diffuse but interrelated group of social psychological theories concerned with when and why individuals identify with, and behave as part of social groups, and adopt shared attitudes. Social identity theory is thus concerned both with the psychological and sociological aspects of group behavior. In this book, the authors present topical research in the study of social identity, including the elderly and social identity; sexual identity in relation to developmental and social considerations; ethnic identity in Baikalian Siberia and the role of Russian colonisation; Latinas and Black women negotiating multiple marginalised social identities; social identity implications for individuals with physical disabilities and social identity and self-image. -- Book Description.